Optimization of Alutsista Procurement Management as a Means of State Defense to Support the Role of The Indonesian’s Army in Implementing Duties - Setiawan, Andi; Ali, Yusuf; Supriyatno, Makmur (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The rapid development of technology is also one of the gaps that can be used as a source of threat to the integrity of a country. Efforts made to maintain the country's integrity need to be supported by defense tools capable of supporting the achievement of these national goals. Developing an independent defense industry is very important in maintaining defense and defense in Indonesia. It is done to meet the needs of both the quality and quantity of defense equipment following the territory of Indonesia and eliminate dependence on other countries in the political field. This study aims to identify and clarify the management process for procuring defense equipment to support TNI personnel in carrying out their duties and increase Indonesia's competitiveness in the global market. In this study, field research was carried out using qualitative methods by reviewing the literature. The research findings show that logistics management in the defense field can support the TNI's role in maintaining the nation's integrity. By modifying the management of defense equipment procurement, the TNI can strengthen its capabilities in carrying out its duties more effectively and efficiently. The findings of this study are expected to guide related parties in making decisions regarding the procurement of defense equipment.